Mitochondrial DNA methylation in metabolic associated fatty liver disease - Mposhi, Archibold; Cortés-Mancera, Fabian; Heegsma, Janette; de Meijer, Vincent E.; van de Sluis, Bart; Sydor, Svenja; Bechmann, Lars P.; Theys, Claudia; de Rijk, Peter; De Pooter, Tim; Vanden Berghe, Wim; İnce, İkbal Agah; et al. (Frontiers in Nutrition, 2023)
Hepatic lipid accumulation and mitochondrial dysfunction are hallmarks of metabolic associated fatty liver disease (MAFLD), yet molecular parameters underlying MAFLD progression are not well understood. Differential methylation within the mitochondrial DNA (mtDNA) has been suggested to be associated with dysfunctional mitochondria, also during progression to Metabolic Steatohepatitis (MeSH). This study further investigates whether mtDNA methylation is associated with hepatic lipid accumulation and MAFLD. The effects of mtDNA methylation on mitochondrial function were investigated by constructing HepG2 cells to stably express mitochondria-targeted viral and prokaryotic cytosine DNA methyltransferases (mtM.CviPI or mtM.SssI for GpC or CpG methylation, respectively). A catalytically-inactive variant (mtM.CviPI-Mut) was constructed as control. Pyrosequencing and Nanopore analysis validated differentially-induced mtDNA hypermethylation for the transgenic HepG2 cell lines. Mitochondrial gene expression and metabolic activity were impaired in HepG2-mtM.CviPI and HepG2-mtM.SssI cells associated with increased lipid accumulation, when compared to the controls. To test whether lipid accumulation causes mtDNA methylation, HepG2 cells were subjected to one or two weeks of fatty acid treatment, but no clear differences in mtDNA methylation were detected. In contrast in vivo, hepatic ND6 mitochondrial cytosine methylation and ND6 gene expression was increased in mice fed a high-fat high cholesterol diet (HFC for 6 or 20 weeks) and in patients with simple steatosis, when compared to controls, while mtDNA content was unchanged. This study supports a role for mtDNA methylation in promoting mitochondrial dysfunction and impaired lipid metabolism in MAFLD.